2017
DOI: 10.1038/s41598-017-09982-9
|View full text |Cite
|
Sign up to set email alerts
|

Fe-based hybrid electrocatalysts for nonaqueous lithium-oxygen batteries

Abstract: Lithium–oxygen batteries promise high energy densities, but are confronted with challenges, such as high overpotentials and sudden death during discharge–charge cycling, because the oxygen electrode is covered with the insulating discharge product, Li2O2. Here, we synthesized low–cost Fe–based nanocomposites via an electrical wire pulse process, as a hybrid electrocatalyst for the oxygen electrode of Li–O2 batteries. Fe3O4-Fe nanohybrids–containing electrodes exhibited a high discharge capacity (13,890 mA h gc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…We investigated EIS analysis for a more secure approach (Figure S10 and Table S1 in the Supporting Information). In the Li–O 2 battery, the semicircle in the middle frequency region indicates the charge transfer resistance ( R ct ), which is associated with the charge transfer reaction at the electrode/electrolyte interface …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated EIS analysis for a more secure approach (Figure S10 and Table S1 in the Supporting Information). In the Li–O 2 battery, the semicircle in the middle frequency region indicates the charge transfer resistance ( R ct ), which is associated with the charge transfer reaction at the electrode/electrolyte interface …”
Section: Resultsmentioning
confidence: 99%
“…In the Li−O 2 battery, the semicircle in the middle frequency region indicates the charge transfer resistance (R ct ), which is associated with the charge transfer reaction at the electrode/ electrolyte interface. 41 R ct is related to the rate coefficient of the chemical reaction in the oxygen electrode. Decreased R ct represents an efficient oxygen diffusion pathway and less agglomeration of the oxygen electrode.…”
Section: •−mentioning
confidence: 99%
“…After the subsequent charge process, the Ru‐CuO/RuO 2 @CC cell again has a smaller R ct (40.3 Ω cm −2 ) than the CuO/RuO 2 ‐P@CC cell (68.5 Ω cm −2 ). Since R ct is inversely proportional to the rate coefficient of chemical reaction, porosity, and O 2 concentration in the cathode, 38‐41 the decrease in R ct indicates that the oxygen diffusion pathway is facilitated by the porous structure of the Ru‐CuO/RuO 2 @CC. During ORR process, the reduced oxygen species (O 2 + n e − → O 2 n − , n = 1 or 2) diffuse in active contact area between the catalyst and the electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed above, the morphology and physicochemical property of discharge product can effectively influence the charging performance of Li-O 2 batteries. Some pioneer works have revealed that catalysts determined the deposition process and finally affected the morphology of discharge product by the different adsorption ability toward LiO 2 intermediate [93][94][95][96]. Adopting such strategy, several relative works were published.…”
Section: Adsorption Of Discharging Intermediate Liomentioning
confidence: 99%